2021
DOI: 10.20870/oeno-one.2021.55.2.4598
|View full text |Cite
|
Sign up to set email alerts
|

Proximal sensing of vineyard soil and canopy vegetation for determining vineyard spatial variability in plant physiology and berry chemistry

Abstract: Proximal sensing is used in vineyards to precisely monitor and manage spatial and temporal variability while reducing laborious and repetitive measurements. Soil electrical conductivity (EC) and canopy vegetation indexes are two frequently assessed variables with off-the-shelf sensors. In this study, the ecophysiological variability of a commercial vineyard comprising three varieties in three blocks, Cabernet-Sauvignon (CS), Cabernet franc (CF), and Petit Verdot (PV), was investigated. Random sampling was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…It is evident that AOS sensors have great potential to be explored in coffee farming; the present study sought to provide an initial approach regarding the potential of using such sensors for PA management. Future studies may address the use of sensors in other scenarios (e.g., crops with different row orientations, mountain coffee, shaded coffee), as well as exploiting this information to create management strategies that optimize the management of inputs, as was done for annual crops [3,13,19,21]. The spatio-temporal evaluation of coffee yield also showed that, in a single field, there may exist coffee plants with inverted bienniality (Figures 7 and 8).…”
Section: In Comparison With Y2mentioning
confidence: 98%
See 1 more Smart Citation
“…It is evident that AOS sensors have great potential to be explored in coffee farming; the present study sought to provide an initial approach regarding the potential of using such sensors for PA management. Future studies may address the use of sensors in other scenarios (e.g., crops with different row orientations, mountain coffee, shaded coffee), as well as exploiting this information to create management strategies that optimize the management of inputs, as was done for annual crops [3,13,19,21]. The spatio-temporal evaluation of coffee yield also showed that, in a single field, there may exist coffee plants with inverted bienniality (Figures 7 and 8).…”
Section: In Comparison With Y2mentioning
confidence: 98%
“…Unlike annual crops, active optical sensing for coffee should be performed with equipment turned to the side view of the plants, since positioning the sensor at the top of the plant is unfeasible due to the canopy height. Although the lateral positioning of active sensors was already adopted in some studies monitoring perennial crops [19][20][21], there is still a need to establish an optimized protocol for the acquisition and processing of these data for coffee crops in order to evaluate its spatial variability over its biennial cycle. For example, in crops with planting lines oriented in an east-west direction, there is no consensus on using data from only one of the side faces (i.e., using only the face that does not receive direct sunlight) or whether the best strategy is to use a methodology to calculate the average of both faces.…”
Section: Introductionmentioning
confidence: 99%
“…Leeuwen et al, 2010;Yu et al, 2021a). This method takes advantage of13 C discrimination in C 3 plants:…”
mentioning
confidence: 99%
“…It is evident that AOS sensors have a great potential to be explored in coffee farming, and that the present study sought to provide an initial approach regarding the potential of using these sensors for PA management. Future studies may address the use in other scenarios (e.g., crops with different row orientation, mountain coffee, shaded coffee), as well as exploiting this information to create management strategies that optimize the management of inputs, as has been done for annual crops TREVISAN et al, 2018;PALLOTTINO et al, 2019;YU et al, 2021).…”
Section: In Comparinson With Y2mentioning
confidence: 99%
“…Unlike annual crops, AOS sensing for coffee should be performed with equipment turned to the side view of the plants since positioning the sensor at the top of the plant is unfeasible due to the height of the canopy. Although the lateral positioning of active sensors has already been adopted in some studies that monitored perennial crops DARRA et al, 2021;YU et al, 2021), there is still a need to establish an optimized protocol for the acquisition and processing of these data for coffee crop in order to evaluate its spatial variability over its biennial cycle. For example, in crops with planting lines oriented in an east-west direction, there is no consensus on using data from only one of the side faces (e.g., using only the face that does not receive direct sunlight) or if the best strategy is to use a methodology to calculate the average of both faces.…”
Section: Introductionmentioning
confidence: 99%